Teacher-related factors as correlates of secondary school students’ achievement in Economics, Ekiti State, Nigeria. (2015)
The development of any nation depends largely on the quality of education of such a nation. Education in Nigeria is generally believed to have fallen in standard, specifically at secondary school level, which is perennially reflected on the academic performance of students in external examinations in all subjects, including Economics. Much effort has been made by all stakeholders with little impact The feet that teachers play crucial roles in students’ achievement is not in doubt hence, this study examined the correlation among Economics teachers’ competence, teaching methods and personality traits and senior secondary school students’ achievement in Economics. Three research questions were formulated. The study adopted descriptive research design of correlational type using multistage sampling technique to select sample from 6 Local Government Areas in Ekiti State. Three instruments were used to collect data, after they have been validated. Data collected were analysed using multiple regression. The findings of the study revealed that positive linear relationship existed between the predictor variables and the criterion variable. The three predictors’ variables accounted for 33.1% of the total variances in students’ achievement in Economics. Teachers’ teaching method, (P = 0.02; P < 0.05), teachers’ competence, (p = 0.84; P< 0.05) and personality traits (P = 0.28; P < 0.051 were significant Based on the findings, it was recommended that teachers should engage in effective teaching of Economics by employing activity-based teaching methods; update their level of competence for better academic achievement in Economics, among others.